The effect of acute fluid consumption and hydration status on percent body fat and minimum wrestling weight - Cutrufello, P. T.; Dixon, C. B. (The Journal of Strength and Conditioning Research, 2013)
The weight certification program for wrestling requires a urine-specific gravity (USG) <1.020. However, the effect of acute rehydration on percent body fat (%BF) and minimum wrestling weight (MWW) is largely unknown. We examined the effect of acute fluid consumption on %BF and MWW. Twenty-five male subjects (18-22 years) were tested in a dehydrated state (USG > 1.020; DEH), 1 hour after rehydration (USG < 1.020; REH), and on a separate day in a hydrated state (USG < 1.020; HYD) which served as the criterion. Percent body fat was determined using skinfolds (SF), air displacement plethysmography (ADP), leg-to-leg bioelectrical impedance analysis (LBIA), and multifrequency bioelectrical impedance analysis (MBIA). Regardless of hydration state, %BF values were not significantly different when using SF (DEH = 13.35 ± 4.03%; REH = 13.41 ± 3.99%; HYD = 13.47 ± 4.31%; p = 0.693) or ADP (DEH = 15.68 ± 4.69%; REH = 16.19 ± 4.57%; HYD = 15.88 ± 4.72%; p = 0.145). The MWW after fluid consumption (REH) was similar to the criterion (HYD) when using SF (REH = 72.04 ± 8.25 kg; HYD = 72.23 ± 8.15 kg; p = 1.000) and ADP (REH = 70.38 ± 8.93 kg; HYD = 70.81 ± 8.50 kg; p = 0.177) methods. Conversely, hydration state had a significant impact on LBIA (p = 0.011) and MBIA (p < 0.001) %BF values resulting in reduced MWWs. When using the SF and ADP methods to assess %BF, modest amounts of water (~1 L) restored euhydration (<1.020) without negatively affecting %BF or MWW. Therefore, acute fluid consumption (~1 L) may offer a safe alternative in which the weight certification program can be expedited.